2021
DOI: 10.7600/jpfsm.10.51
|View full text |Cite
|
Sign up to set email alerts
|

Stair climbing–descending exercise following meals improves 24-hour glucose excursions in people with type 2 diabetes

Abstract: We aimed at evaluating the effect of short-duration stair climbing-descending exercise (ST-EX) on 24-hour blood glucose (BG) response in people with type 2 diabetes (T2D). Seven men (age, 70.1 ± 1.3 years) with uncomplicated T2D consumed three meals per day according to a meal plan for patients with diabetes. Participants completed one session of ST-EX 60 and 120 min after each meal on the first day (ST-EX day), and did not perform ST-EX on the following day (REST day). Each ST-EX session comprised two 3-min b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…[ 33 ] Appropriate PA can improve the symptoms of arteriosclerosis in the middle-aged and elderly, restore the arteries of the elderly to normal function, and then reduce the risk of stroke in the middle-aged and elderly. [ 34 ] Appropriate PA can improve or repair the function of the sympathetic nervous system, thereby restoring the body’s control over the normal function of the cardiovascular system, keeping the body’s heart rate and blood pressure within the normal range, and reducing the risk of stroke in the elderly. [ 35 ] The abnormal glucose metabolism and islet function of human body will increase the risk of stroke, [ 36 ] while physical exercise will improve the glucose metabolism and islet function of human body.…”
Section: Discussionmentioning
confidence: 99%
“…[ 33 ] Appropriate PA can improve the symptoms of arteriosclerosis in the middle-aged and elderly, restore the arteries of the elderly to normal function, and then reduce the risk of stroke in the middle-aged and elderly. [ 34 ] Appropriate PA can improve or repair the function of the sympathetic nervous system, thereby restoring the body’s control over the normal function of the cardiovascular system, keeping the body’s heart rate and blood pressure within the normal range, and reducing the risk of stroke in the elderly. [ 35 ] The abnormal glucose metabolism and islet function of human body will increase the risk of stroke, [ 36 ] while physical exercise will improve the glucose metabolism and islet function of human body.…”
Section: Discussionmentioning
confidence: 99%
“…[ 26 ] Abnormal glucose metabolism and islet function in the human body will increase the body’s risk of hypertension, [ 27 ] while physical exercise will improve the body’s glucose metabolism and islet function. [ 28 ] Physical exercise can further improve the body’s regulation of blood pressure by improving the glucose metabolism and islet function, to stabilize blood pressure in the normal range. The damaged structure and function of the left ventricle in human body will lead to ischemia under the endocardium and coronary artery stenosis, which will lead to hypertension in the body.…”
Section: Discussionmentioning
confidence: 99%
“…The average body mass index (BMI) of all participants in all studies combined was 30 kg·m −2 . Of the 31 selected studies, 21 recruited patients with T2DM [26,[28][29][30][31][32][33][34][35][36][37][38][47][48][49][50][51][52][53][54][55], while the remaining 10 studies involved overweight and obese participants [39,[56][57][58][59][60][61][62][63][64]. Of those 21 studies on patients with T2DM, 3 included patients that were treated with exogenous insulin [34][35][36], while the rest allowed their participants to use glucose-lowering medications but instructed them to keep the same dosage throughout the study period.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…However, this view is based on a limited number of studies that mainly compare the effect of pre-and post-meal exercise on glycemic responses in individuals with T2DM [26][27][28]. Studies involving an exercise regimen 60 min or more after a meal have also shown a significant reduction in glucose response in this population [29][30][31][32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%